2007
DOI: 10.1037/0021-843x.116.2.342
|View full text |Cite
|
Sign up to set email alerts
|

Is there more to complicated grief than depression and posttraumatic stress disorder? A test of incremental validity.

Abstract: There is growing interest in complicated grief reactions as a possible new diagnostic category for inclusion in the Diagnostic and Statistical Manual of Mental Disorders. However, no research has yet shown that complicated grief has incremental validity (i.e., predicts unique variance in functioning). The authors addressed this issue in 2 studies by comparing grief, depression, and posttraumatic stress disorder (PTSD) symptoms with different measures of functioning (interviewer ratings, friend ratings, self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
181
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(217 citation statements)
references
References 65 publications
33
181
1
2
Order By: Relevance
“…Furthermore, PTSD often involves more pronounced anxiety, especially when confronted with the threat that is related to the traumatic event, on the other hand, the bereaved people experience separation anxiety with some elements of comfort when confronted with memories of the deceased (Lichtenthal et al, 2004). The findings were supported by two studies by Bonanno et al (2007) who compared CG, depression and PTSD, and found that CG predicted functioning in the bereaved over and above PTSD and depression. They also found that both PTSD and CG predicted cardiovascular responsivity, however they concluded that PTSD four months post loss predicted increased heart rate when interviewed about the lost relationship, while CG predicted decreased heart rate (Bonanno et al, 2007).…”
Section: Ptsd Depression and Complicated Griefsupporting
confidence: 70%
See 1 more Smart Citation
“…Furthermore, PTSD often involves more pronounced anxiety, especially when confronted with the threat that is related to the traumatic event, on the other hand, the bereaved people experience separation anxiety with some elements of comfort when confronted with memories of the deceased (Lichtenthal et al, 2004). The findings were supported by two studies by Bonanno et al (2007) who compared CG, depression and PTSD, and found that CG predicted functioning in the bereaved over and above PTSD and depression. They also found that both PTSD and CG predicted cardiovascular responsivity, however they concluded that PTSD four months post loss predicted increased heart rate when interviewed about the lost relationship, while CG predicted decreased heart rate (Bonanno et al, 2007).…”
Section: Ptsd Depression and Complicated Griefsupporting
confidence: 70%
“…The findings were supported by two studies by Bonanno et al (2007) who compared CG, depression and PTSD, and found that CG predicted functioning in the bereaved over and above PTSD and depression. They also found that both PTSD and CG predicted cardiovascular responsivity, however they concluded that PTSD four months post loss predicted increased heart rate when interviewed about the lost relationship, while CG predicted decreased heart rate (Bonanno et al, 2007).…”
Section: Ptsd Depression and Complicated Griefsupporting
confidence: 70%
“…Items assess reexperiencing of the trauma, emotional numbing, avoidance of trauma-related reminders, and heightened arousal. The PCL-C has shown high reliability in previous samples of bereaved individuals [21], and, also in our study, at T1 (α = 0.92) and T2 (α = 0.96).…”
Section: Ptsd Checklist-civilian Version (Pcl-c; [58])mentioning
confidence: 55%
“…However, other forms of distress, such as posttraumatic stress disorder (PTSD; [2]) and CG [3] have been shown to have incremental validity in terms of predicting bereavement outcome [16,21,22]. Thus, a more comprehensive assessment of adaptation following loss should include depressive, post-traumatic, and complicated grief symptomatology.…”
Section: Bereavement Outcomesmentioning
confidence: 99%
“…For example, Prolonged Grief Disorder (PGD), which is a protracted, clinically significant, and functionally impairing form of grief, is experienced by 10–15% of those grieving a non-violent death (Lundorff, Holmgren, Zachariae, Farver-Vestergaard, & O’Connor, 2017; Prigerson et al, 2009) as compared with 30–70% of those grieving a violent death (McDevitt-Murphy et al, 2012; Mitchell, Kim, Prigerson, & Mortimer-Stephens, 2004; Momartin, Silove, Manicavasagar, & Steel, 2004; Shear, Jackson, Essock, Donahue, & Felton, 2006). PGD has been differentiated from Post-Traumatic Stress Disorder (PTSD) and post-loss depression (Boelen & Van Den Bout, 2005; Bonanno et al, 2007; Lichtenthal, Cruess, & Prigerson, 2004). It is referred to as Persistent Complex Bereavement Disorder under the section on conditions for further study in the DSM-5 (American Psychological Association, 2013), and will be introduced as a mental health diagnosis in the ICD-11 (World Health Organization, 2018; Maciejewski, Maercker, Boelen, & Prigerson, 2016).…”
mentioning
confidence: 99%